2015
DOI: 10.1038/ncomms8000
|View full text |Cite
|
Sign up to set email alerts
|

Widespread seasonal gene expression reveals annual differences in human immunity and physiology

Abstract: Seasonal variations are rarely considered a contributing component to human tissue function or health, although many diseases and physiological process display annual periodicities. Here we find more than 4,000 protein-coding mRNAs in white blood cells and adipose tissue to have seasonal expression profiles, with inverted patterns observed between Europe and Oceania. We also find the cellular composition of blood to vary by season, and these changes, which differ between the United Kingdom and The Gambia, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
369
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(440 citation statements)
references
References 71 publications
40
369
3
3
Order By: Relevance
“…A recent study has demonstrated seasonal variation in gene expression in human lymphocytes and adipocytes (36) . These cell types play important roles in insulin sensitivity and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated seasonal variation in gene expression in human lymphocytes and adipocytes (36) . These cell types play important roles in insulin sensitivity and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…lular and cytokine levels may not just fluctuate on a daily basis, but may also display seasonal variation. In humans white blood cell numbers peak in the winter months, correlating with a profound pro-inflammatory transcriptomic profile [64]. C-reactive protein peaks during the winter, which is a biomarker for inflammatory diseases [64].…”
Section: Circadian Disruption and Diseasementioning
confidence: 99%
“…In humans white blood cell numbers peak in the winter months, correlating with a profound pro-inflammatory transcriptomic profile [64]. C-reactive protein peaks during the winter, which is a biomarker for inflammatory diseases [64]. Seasonality in clock gene expression is also observed, including Bmal1, which was shown to peak during the summer and trough during the winter [64].…”
Section: Circadian Disruption and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations in host-pathogen interactions are common in nature (6). In humans, the immune system undergoes substantial seasonal changes in gene expression, which is inverted between European locations and Oceania (7). The regulation of seasonal changes in both disease incidence and immune defense is known to interact with environmental factors, such as annual changes in day length, humidity, and ambient temperature (8).…”
mentioning
confidence: 99%